Selective oropharyngeal decontamination versus selective digestive decontamination in critically ill patients: a meta-analysis of randomized controlled trials - Zhao D; Song J; Gao X; Gao F; Wu Y; Lu Y; Hou K (Dove Medical Press, 2015)
Di Zhao,1,* Jian Song,2,* Xuan Gao,3 Fei Gao,4 Yupeng Wu,2 Yingying Lu,5 Kai Hou1 1Department of Neurosurgery, The First Hospital of Hebei Medical University, 2Department of Neurosurgery, 3Department of Neurology, The Second Hospital of Hebei Medical University, 4Hebei Provincial Procurement Centers for Medical Drugs and Devices, 5Department of Neurosurgery, The Second Hospital of Hebei Medical University, Shijiazhuang People’s Republic of China *These authors contributed equally to this work Background: Selective digestive decontamination (SDD) and selective oropharyngeal decontamination (SOD) are associated with reduced mortality and infection rates among patients in intensive care units (ICUs); however, whether SOD has a superior effect than SDD remains uncertain. Hence, we conducted a meta-analysis of randomized controlled trials (RCTs) to compare SOD with SDD in terms of clinical outcomes and antimicrobial resistance rates in patients who were critically ill. Methods: RCTs published in PubMed, Embase, and Web of Science were systematically reviewed to compare the effects of SOD and SDD in patients who were critically ill. Outcomes included day-28 mortality, length of ICU stay, length of hospital stay, duration of mechanical ventilation, ICU-acquired bacteremia, and prevalence of antibiotic-resistant Gram-negative bacteria. Results were expressed as risk ratio (RR) with 95% confidence intervals (CIs), and weighted mean differences (WMDs) with 95% CIs. Pooled estimates were performed using a fixed-effects model or random-effects model, depending on the heterogeneity among studies. Results: A total of four RCTs involving 23,822 patients met the inclusion criteria and were included in this meta-analysis. Among patients whose admitting specialty was surgery, cardiothoracic surgery (57.3%) and neurosurgery (29.7%) were the two main types of surgery being performed. Pooled results showed that SOD had similar effects as SDD in day-28 mortality (RR =1.03; 95% CI: 0.98, 1.08; P=0.253), length of ICU stay (WMD =0.00 days; 95% CI: -0.2, 0.2; P=1.00), length of hospital stay (WMD =0.00 days; 95% CI: -0.65, 0.65; P=1.00), and duration of mechanical ventilation (WMD =1.01 days; 95% CI: -0.01, 2.02; P=0.053). On the other hand, compared with SOD, SDD had a lower day-28 mortality in surgical patients (RR =1.11; 95% CI: 1.00, 1.22; P=0.050), lower incidence of ICU-acquired bacteremia (RR =1.38; 95% CI: 1.24, 1.54; P=0.000), and lower rectal carriage of aminoglycosides (RR =2.08; 95% CI: 1.68, 2.58; P=0.000), ciprofloxacin-resistant Gram-negative bacteria (RR =1.84; 95% CI: 1.48, 2.29; P=0.000), and respiratory carriage of third-generation cephalosporin-resistant Gram-negative bacteria (RR =2.50; 95% CI: 1.78, 3.5; P=0.000). Conclusion: SOD has similar effects as SDD in clinical outcomes, but has higher incidence of ICU-acquired bacteremia, and higher carriage of antibiotic-resistant Gram-negative bacteria. However, due to the high cost of SDD and the increased risk of development of antibiotic resistance with the widespread use of cephalosporins in SDD, we would recommend SOD as prophylactic antibiotic regimens in patients in the ICU. More well-designed, large-scale RCTs are needed to confirm our findings. Keywords: selective digestive decontamination, selective oropharyngeal decontamination, intensive care units, meta-analysis